DEVELOPING ENTERPRISE ARCHITECTURE FOR BPRACO SMEs DIGITAL TRANSFORMATION BY USING TOGAF 10 - Shintya Rahma Safitri; Rahmat Mulyana; Asti Amalia Nur Fajrillah (JIKO (Jurnal Informatika dan Komputer), 2024)
Organizations must embrace emerging technology through Digital Transformation (DT) to remain competitive in the digital revolution era. While previous research has highlighted the critical role of DT strategy and architecture in driving DT success in large banks, these insights have not been thoroughly tested in small-scale banks. Small and medium-sized enterprise (SME) banks like BPR often encounter significant challenges in the DT journey, including limited infrastructure, reliance on outdated and poorly integrated systems, and slow technology adoption. These barriers hinder their ability to support the DT initiatives necessary for thriving in the digital age. This study aims to develop an enterprise architecture blueprint tailored to support DT in BPRACo, an SME-scale bank. The research follows a five-stage Design Science Research (DSR) methodology, encompassing problem explication, requirement specification, design and development, demonstration, and evaluation. Data were collected through semi-structured interviews, validated through document triangulation, and analyzed using the TOGAF 10 framework, covering phases from preliminary planning to migration. The resulting blueprint was integrated into BPRACo's DT Strategy for 2024-2026. This research enhances the understanding of enterprise architecture's role in DT within the context of SME banks. It offers practical guidance for BPRACo and similar institutions to implement prioritized enterprise architecture artifacts, facilitating a successful DT journey.